Cage hydrocarbons as linkers in dimeric drug design: Case studies with trimethoprim and tedizolid. (15th January 2023) - Vujcic, Biljana; Wyllie, Jessica; Tania,; Burns, Jed; White, Keith F.; Cromwell, Simon; Lupton, David W.; Dutton, Jason L.; Soares da Costa, Tatiana P.; Houston, Sevan D.
Graphical abstract: Abstract: The looming threat of a "post-antibiotic era" has been caused by a rapid rise in antibacterial resistance and subsequent depletion of effective antibiotic agents in the clinic. An efficient strategy to address this shortfall lies in the reengineering of pre-existing and commercially available antibiotic drugs. This is exemplified by dimerization, a design concept in which two pharmacophores are covalently linked to form a new chemical entity. The cage hydrocarbons cubane (1 ), bicyclo[2.2.2]octane (BCO) (2 ), adamantane (3 ), and bicyclo[1.1.1]pentane (BCP) (4 ) present themselves as an attractive family of linkers in this regard. In this report, all four hydrocarbon cages were employed as linkers in a series of dimers based on the commercially available antibiotics trimethoprim and tedizolid. A detailed synthetic roadmap for the protection and deprotection of each pharmacophore is outlined. Several members of the trimethoprim series showed activity on par with that of their trimethoprim progenitor, although this was not the case for the tedizolid series. The design strategy outlined herein highlights the utility of the group as a platform for the rapid and modular construction of future novel antibiotics.